Polypill therapy and frailty in elderly: Time to stop treating everything - Kumar, Sunil; Godhiwala, Parth; Garikapati, Amrutha; Jain, Shraddha (Asian Journal of Medical Sciences, 2021)
Background: Frailty is a reversible age-related condition of increased vulnerability and risk of death or unplanned hospitalization. Frailty and polypill therapy are common in elderly, although little is known about the impact, they may have on each other. Aims and Objective: The study was a prospective observational study, designed with an aim to observe the six-month and one-year outcomes of elderly patients on polypill therapy. Material and Methods: Three hundred forty-two patients aged more than 60 years on polypill treatment were enrolled in this study, which were on regular follow up in our rural hospital at geriatric units of medicine department. Results: At the end of one year, 38.1% were in severe frailty (FIRE >0.7) category, out of which death happened at the end of one year were 41.6%. 47.6% required repeated hospitalisations that were on polypill therapy. Conclusions: A reduction of polypill therapy could be a cautious strategy to prevent and manage frailty. Further research is needed to confirm the possible benefits of reducing polypill in the development, reversion or delay of frailty.